Priesthood of The Baptised and of the Ordained: Correlated but Different - Puthenveettil, Jos (Asian Horizons, 2009)
In the Year for Priests, priesthood is the prime topic of reflection and discussion in the whole Church and to some extent also in the society. As we study the origin and development of priesthood, we realize that the term ‘priest’ or ‘priesthood’ is used in three different ways in Christian tradition: 1) The priesthood of Jesus Christ; 2) the priesthood of the baptised; and 3) the priesthood of the ordained. The New Testament, however, uses the term ‘priest’ only in connection with the first two senses. Firstly, in the Letter to the Hebrews, the priestly identity and mission of Jesus Christ is well depicted. Accordingly, Jesus Christ is the priest or the ‘High Priest’ par excellence, though He never called himself a priest. His redemptive ministry of service, culminating in his death and resurrection, is the definitive act of priesthood, offering authentic obedient worship to God and atoning for the sins of the humanity. Secondly, the first Epistle of St. Peter refers to the priesthood of all the Christians. They are the priestly people of God who are called to share in the priesthood of Christ in view of continuing His redemptive mission of establishing the Kingdom of God. However, in the New Testament, we do not see any explicit reference to the priesthood of the ordained.